Implementasi Budaya Sekolah dalam Pembinaan Karakter Siswa - Frasandy, Rendy; Ardipal; Desyandri (Institut Agama Islam Negeri Madura, 2024)
This research is motivated by the early behavior shown by children in their childhood. Like, say dirty and theft. Parents' indifference about their child's behavior makes the child's character worse. Therefore, a solution is needed to foster character for children through positive habits that are able to build character gradually. From this, the role of educational institutions such as school is to foster student character through the school culture in it. The objectives to be achieved in this study are to describe the character values and school culture in implementing school culture in fostering student character at school. This study uses a qualitative descriptive type, where the researcher tries to describe in full the phenomena that occur systematically. The data collection method used by researchers is a structured interview method for students and unstructured for principals and classroom teachers. In addition to the interview method, the researcher also uses the method of observation and documentation in this study. The results of this study indicate that the implementation of school culture in fostering student character shows significant results. This can be seen from the daily behavior of students both at school and at home. The characters in question are religious, honest, disciplined, independent, love the homeland, and so on. Of course, this was achieved thanks to the support of various parties, especially parents.